Irregularities Observed at the Edge of a Mid‐Latitude Ionospheric Depletion Following a Geomagnetic Storm - J. F. Helmboldt (Space Weather)
Abstract This manuscript presents the analysis of data from multiple ground‐ and space‐based sensors in the North American region before, during, and after the 12 October 2021 geomagnetic storm. Total electron content (TEC) and electron density data show the formation and equatorward propagation of a mid‐latitude trough at ∼50°N followed by the appearance of a wider depletion region (∼15° in latitude) at lower latitudes. During the recovery phase on the 13th, the equatorward edge of this depletion region settled at around 30° latitude and exhibited a steep density gradient. By the 14th, this sharp boundary had disappeared. Near this edge on the 13th, small‐scale irregularities formed. The impact of these was observed within Global Positioning System data as elevated rate of TEC index (ROTI) and presented as strong 35 MHz scintillations of cosmic radio sources as well as spread‐F within ionograms from multiple digisonde systems. GPS and 35‐MHz data demonstrated that the irregularity region was narrowly confined (≲5° wide) near the edge of the depletion region. The 35‐MHz scintillation data also showed that the irregularities were moving relatively slowly at ∼7 m s−1, likely toward the southeast. Density and velocity measurements demonstrated that the conditions near the depletion boundary were highly favorable to the gradient drift instability (GDI) with the one‐dimensional growth rate estimated to be ∼0.01 s−1. Since these conditions persisted for many hours, this growth rate was more than sufficient for the GDI to be considered the primary driver of irregularity formation in this case.